Caçadores de symbolos : (estudos literarios) - Grieco, Agrippino, (A grande Livraria Leite Ribeiro, 1923)
Conteúdo : Pereira da Silva. - Théo-Filho. - Ronald de Carvalho. - Tristão de Athayde. - Hermes Fontes. - Enéas Ferraz. - Luiz Carlos. - J. Geraldo Vieira. - Raul de Leoni. - Renato Almeida.